Spotlight on Ferroptosis: Iron-Dependent Cell Death in Alzheimer’s Disease - Ashraf, Azhaar; So, Po-Wah (Frontiers in Aging Neuroscience, 2020)
Alzheimer’s disease is an emerging global epidemic that is becoming increasingly unsustainable. Most of the clinical trials have been centered around targeting β-amyloid and have met with limited success. There is a great impetus to identify alternative drug targets. Iron appears to be the common theme prevalent across neurodegenerative diseases. Iron has been shown to promote aggregation and pathogenicity of the characteristic aberrant proteins, β-amyloid, tau, α-synuclein, and TDP43, in these diseases. Further support for the involvement of iron in pathogenesis is provided by the recent discovery of a new form of cell death, ferroptosis. Arising from iron-dependent lipid peroxidation, ferroptosis is augmented in conditions of cysteine deficiency and glutathione peroxidase-4 inactivation. Here, we review clinical trials that provide the rationale for targeting ferroptosis to delay the pathogenesis of Alzheimer’s disease (AD), potentially of relevance to other neurodegenerative diseases.